Hot-rolled steel strip for photovoltaic racks and method for manufacturing the same
Patent Information
- Application Number
- CN202311623120.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-30
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-11-30
AI Technical Summary
[0013]当前关于Q235高效生产技术,大多是通过工艺手段,优化生产流程,用以提高钢板或钢带本身性能,针对客户后续冷轧-退火-热镀-冷弯成型-焊接等使用要求而专项研发的相关技术较少,有鉴于此,本发明提出一种低成本高性能光伏支架专用Q235热轧钢带及其制备方法,整个工艺流程简单易实施,在不增加生产成本或少增加生产成本的条件下,升级Q235钢带性能,使之可作为原料经冷轧-退火-热镀锌/锌铝镁-冷弯成型制造光伏支架,提高钢带的整体性能及附加值,解决传统Q235钢因成分、工艺及各钢厂装备水平及设计差异宽泛,导致生产钢带如用以制造光伏支架时可能带来的各类问题
[0032]1、本发明提供了一种低成本、易实现的低碳、低硅、微锰、微钛的成分体系,在保证钢带基础强度的基础上,具备较高的表面质量及较软的可轧性,为后续冷轧、镀锌铝镁/锌铝/锌创造了较好的控制条件。本成分设计均避开了中、高碳成分设计时碳含量落在包晶区时可能出现的热裂纹隐患,保证了较好的铸坯边部、角部质量,铸坯无需落地精整,直接线上热装炉,降低了能耗并缩短工艺流程。同时,避免了因碳含量较高时对应冷轧工序可能出现的冷轧变形抗力大,小载荷轧机“吃不动”,轧制节奏稳定性差,轧制效率低等问题。并且,与之对应的是,本成分设计并未因要获得较高的冷轧条件,过度追求超低碳,当下钢厂获得超低碳,大多需要通过RH深脱碳工序,导致流程冗长,且需添加更多锰、钛等合金,弥补强度损失,增加工艺及合金成本。本成分设计成本低廉,操作流程简单,符合国内大多数钢厂炼钢实际,可推广性强。
Smart Images

Figure CN117778877B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of microalloyed steel, specifically to a Q235 hot-rolled steel strip for photovoltaic brackets and its preparation method. Background Technology
[0002] Against the backdrop of "dual carbon" goals of carbon peaking and carbon neutrality, energy conservation and carbon reduction, as well as the green and low-carbon transformation of energy, have become the focus of attention. The clean energy industry, such as solar energy, is developing rapidly, with an estimated annual increase of over 70GW in photovoltaic installations. The supporting system for photovoltaic brackets is also developing rapidly. Currently, photovoltaic brackets can be classified into carbon steel brackets, aluminum alloy brackets, stainless steel brackets, and non-metallic brackets based on their manufacturing materials.
[0003] Aluminum alloy bracket, with a base material density of approximately 2.71 g / m³. 2 Its profile deformation is about 2.9 times that of steel, and its strength is about 70% of that of steel. It is protected against corrosion by anodizing and has the characteristics of being lightweight, beautiful, durable and corrosion resistant. However, it has low load-bearing capacity and a high price, about 3 times that of steel.
[0004] Stainless steel brackets are commonly used as bracket frames. They have good weather resistance, but the cost of the base material is relatively high, so they are rarely used in the market.
[0005] Non-metallic scaffolds, with fiber composite materials as the base material, are lightweight, strong, have good stress resistance, and are low in cost. However, as they are new materials, their properties need to be verified in actual projects, and they are currently used less frequently.
[0006] Carbon steel support frame, with a base material density of approximately 7.85 g / m³. 2 60-70% of the base material is made of steel such as Q235 and Q355. Corrosion protection is often achieved by hot-dip galvanizing or zinc-aluminum-magnesium coating. Due to its high mechanical strength, small deflection deformation when bearing load, good stability of support performance, mature manufacturing process, high load-bearing capacity, wide range of application areas, and combination of low cost and high adaptability, it is the most widely used. Currently, the annual steel consumption of supporting photovoltaic supports has exceeded 2.4 million tons.
[0007] Photovoltaic support system design must comprehensively consider factors such as the location's geography, climate, solar energy resources, and support system costs. Currently, the most widely used support base materials are Q235B steel and 6063T6 aluminum alloy extrusion profiles. In terms of strength, 6063T6 aluminum alloy is approximately 68%-69% stronger than Q235B steel. In strong wind areas and large spans, steel is superior to aluminum alloy profiles. Regarding cost, under typical natural conditions, i.e., a basic wind pressure of 0.6 kN / m²... 2 For spans under 2m, the cost of aluminum alloy photovoltaic brackets is 1.3-1.5 times that of steel structure photovoltaic brackets.
[0008] In summary, Q235 and Q355 carbon steel photovoltaic (PV) brackets dominate the PV support system market. However, traditional Q235 steel has a lower yield strength and is heavier under the same load conditions. As environmental requirements for PV system design become increasingly stringent, the rational use of existing building space, saving construction area and reducing costs, is becoming increasingly important in the installation and use of PV systems. Traditional Q235 carbon steel brackets do not offer advantages in this regard and are inconvenient to transport and install. Furthermore, to ensure the corrosion resistance and service life of PV brackets, hot-dip galvanizing / zinc-aluminum-magnesium galvanizing of the base steel strip is currently required. This places high demands on the surface quality of the steel strip. PV bracket steel strip manufacturers often use hot-rolled steel strips through pickling-cold rolling-annealing-hot-dip galvanizing / zinc-aluminum-magnesium galvanizing processes to produce high-quality PV bracket-specific steel strips. The raw material of the hot-rolled steel strip directly determines the performance and surface quality of the final steel strip. To improve the performance of Q235 hot-rolled raw material steel strip without increasing production costs or with minimal increase in production costs, there is an urgent need to develop a low-cost, high-performance Q235 hot-rolled steel strip specifically for photovoltaic brackets and its manufacturing method.
[0009] Q235 steel is one of the most commonly used steel grades, with the following composition standards: C≤0.20%; Mn≤1.4%; Si≤0.35%; S≤0.045%; P≤0.045%. The grade designation consists of "Q" + a number + a quality grade symbol. "Q" represents the yield strength, and the number indicates the specific numerical value of the yield strength in MPa. For example, Q235 indicates a carbon structural steel with a yield strength (σs) of 235 MPa. Due to its low price, Q235 steel is widely used in various industries such as construction, bridges, vehicles, boilers, containers, and shipbuilding.
[0010] With the rapid economic growth, various industries have become more demanding in their requirements for steel materials. The contradiction between overcapacity of ordinary steel grades and shortage of high-performance special-purpose steel grades is becoming increasingly severe in the steel industry. At the same time, the high cost of upstream iron ore and alloys, as well as the problems of overcapacity of ordinary steel products and uncoordinated product structure, are seriously compressing the profit margins of steel companies and restricting their development. Q235 series steel, as the most widely used and applied carbon steel that can be produced by all major steel companies, faces the important historical task of steel industry technicians: how to upgrade product quality and performance without increasing or minimizing costs through reasonable composition design, fine-tuning of element content and rolling process, and developing various high-performance special-purpose steel strips based on the actual production needs of downstream customers.
[0011] Patent application CN 103343209 A discloses a controlled rolling and controlled cooling process for improving the performance of Q235 steel plate. The process is as follows: (1) Smelt and continuously cast billets according to chemical composition. The composition ratio is: C: 0.10~0.20%, Si: ≤0.30%, Mn: 0.30~0.70%, P: ≤0.045%, S: ≤0.045%, the remainder is iron and unavoidable impurities. Smelt and continuously cast billets with a thickness of 115mm; (2) Billet heating: heating temperature is 1100℃, and holding temperature for 1-2h; (3) High temperature rolling: initial rolling temperature is 1000-1100℃; ensure total deformation >80%, and single-pass deformation is not less than 10%; final rolling temperature is controlled at 900℃-950℃; (4) Immediately after rolling, ultra-fast cooling is performed with a cooling rate >100℃ / s; and the final cooling temperature is controlled at 500-600℃, followed by air cooling to room temperature. The prepared Q235 steel plate has a yield strength of 350-365MPa, a tensile strength of 470-495MPa, and an elongation of 25.5-30.5%, showing a significant improvement in performance. However, the process requires strict control of the total deformation and the deformation per pass, and it demands a high level of operational proficiency. Furthermore, the ultra-fast cooling after rolling will affect the coiling process of the steel plate.
[0012] Patent CN 114015929 B discloses a rolling process for titanium-containing low-carbon Q235B steel, with the following composition: C: 0.050-0.070%, Si: ≤0.08%, Mn: 0.38-0.50%, Al: 0.010-0.020%, P: ≤0.020%, S: ≤0.020%, Ti: 0.035-0.045%. The rolling process includes two steps: high-temperature rolling and cooling of the steel strip billet. The final Q235 steel plate produced... With a tensile strength ≥388MPa, elongation ≥39%, this steel strip boasts increased strength, optimized weldability, and improved overall performance. However, its carbon content is relatively low (C: 0.050-0.070%), requiring increased oxygen blowing intensity or the use of low-phosphorus, low-carbon silicon-manganese alloy (approximately 8000 RMB / ton) for deoxidation and alloying, resulting in higher costs compared to commonly used silicon-manganese (approximately 6000 RMB / ton) and medium-manganese alloy (approximately 7000 RMB / ton). Furthermore, this process imposes strict requirements on rolling temperature, cooling temperature, and cooling rate, especially the cooling rate. The cooling water temperature needs to be controlled between 28-42℃. While this is easily maintained in summer due to higher temperatures, it is difficult to maintain this temperature in winter due to low temperatures and the lack of heating equipment for the cooling water. This restricts production and hinders the steel mill's ability to accept orders and maintain downstream customer relationships during winter. If production is forced to continue in winter, the low temperatures and rain / snow, combined with the low cooling water temperature and rapid cooling rate, can easily lead to abnormal structures such as bainite, making it difficult to guarantee the mechanical and cold-bending properties of the final product. Summary of the Invention
[0013] Current technologies for high-efficiency Q235 steel production mostly focus on optimizing production processes to improve the performance of the steel plate or strip itself. However, there are few technologies specifically developed to address customer requirements for subsequent processes such as cold rolling, annealing, hot-dip galvanizing, cold bending, and welding. Therefore, this invention proposes a low-cost, high-performance Q235 hot-rolled steel strip for photovoltaic brackets and its preparation method. The entire process is simple and easy to implement, upgrading the performance of Q235 steel strip with little or no increase in production costs. This allows it to be used as raw material for manufacturing photovoltaic brackets through cold rolling, annealing, hot-dip galvanizing / zinc-aluminum-magnesium galvanizing, and cold bending. This improves the overall performance and added value of the steel strip and solves various problems that may arise when using traditional Q235 steel strips for photovoltaic bracket manufacturing due to the wide differences in composition, processes, and equipment levels and designs among steel mills. For example 1: High silicon content may result in poor surface quality, and missing plating points during hot-dip galvanizing / zinc-aluminum-magnesium galvanizing, affecting the service life of the support; For example 2: High carbon and manganese content may result in high cold rolling deformation resistance, making it difficult for small-load rolling mills to operate, leading to poor rolling rhythm stability and low rolling efficiency; For example 3: In some low-carbon titanium-containing steel strips, excessive nitrogen content or unstable process control leads to the formation of large-sized TiN, resulting in low effective Ti utilization. This not only fails to exert the precipitation strengthening effect of titanium but may even induce inclusions, affecting the purity of the steel matrix and causing practical problems such as insufficient strength and cold bending cracking.
[0014] Specifically, to achieve the above-mentioned objectives, this invention provides a low-cost, high-performance photovoltaic support structure using titanium-containing low-carbon Q235 hot-rolled steel strip. The chemical composition, by mass percentage, includes C: 0.07-0.11%, Si: ≤0.10%, Mn: 0.35-0.50%, P: 0.08-0.1%, S: ≤0.020%, Alt: 0.015-0.045%, Ti: 0.032-0.050%; the balance being iron and unavoidable impurities.
[0015] The steel strip of this invention has a microstructure consisting of a fine, uniformly distributed mixture of ferrite and pearlite. The roles and proportions of the various elements in this invention are based on the following:
[0016] Carbon (C) is an interstitial solid solution element that significantly affects the strength, hardness, and toughness of steel strips. However, since this steel strip is used as a cold-rolled base material for manufacturing photovoltaic brackets through cold rolling, annealing, hot-dip galvanizing / zinc-aluminum-magnesium galvanizing, and cold bending, excessively high C content in the base steel can lead to an increase in the thickness of the Fe-Zn alloy layer, resulting in decreased adhesion of the galvanized layer and even inducing brittle cracks. Therefore, the C content should be controlled between 0.07% and 0.11%.
[0017] Si (Silicon): A common deoxidizing element in steel, soluble in ferrite and austenite, it possesses a certain solid solution strengthening effect, significantly improving the strength of the steel matrix. However, excessive Si content can cause defects such as thick hot-dip galvanized layers, poor adhesion, and severe color differences during anti-corrosion galvanizing / zinc-aluminum-magnesium plating. In severe cases, it can even lead to incomplete galvanizing, increasing zinc consumption and reducing service life. Therefore, the Si content should be controlled at ≤0.10%.
[0018] Mn plays a role in solid solution strengthening, increasing the strength and toughness of steel and improving its hot working properties. However, manganese has a strong tendency to segregate, easily producing elongated MnS plastic inclusions during rolling production, resulting in significant differences in longitudinal and transverse mechanical properties, severe banded structure, and excessively high manganese content weakens the corrosion resistance of the steel matrix, deteriorates weldability, and increases alloy costs. Therefore, the Mn content is controlled at 0.35-0.50%.
[0019] P (Polymer) is a harmful element in smelting, severely damaging the toughness and plasticity of steel. However, since the thickness of steel strips used to manufacture photovoltaic brackets is generally less than 2mm after cold rolling, the uneven deformation of the inner and outer surfaces of extremely thin steel during bending and forming is small, and the elongation at the bends is small. Therefore, extremely thin steel is less prone to cold bending cracks. The requirements for the toughness and plasticity of steel used in photovoltaic brackets are low, while corrosion resistance is the most important performance consideration. P can help improve the corrosion resistance of steel. According to the dry and wet alternating corrosion resistance test, for every 0.02% increase in P content, the corrosion resistance of steel (expressed as a reduction in steel weight) increases by 50%. When the P content in the steel is controlled to reach more than 0.08% in this invention, the corrosion resistance of the photovoltaic bracket is more than twice that of existing steel, which can reduce the amount of galvanizing, reduce the thickness of the galvanized layer by 50%, save zinc liquid consumption, and reduce the galvanizing cost by 20 yuan / ton of steel. Furthermore, the amount of dephosphorizing lime added to the converter is reduced by more than 50%, and the basicity of the converter slag at the end point can be controlled at 1 to 1.5. This reduces the amount of dephosphorizing lime added to the converter by more than 15 kg / ton, and lowers the smelting cost by 20 yuan / ton of steel. Therefore, the P content is controlled at 0.08 to 0.1%.
[0020] S: Excessive sulfur content can cause hot brittleness, which can easily lead to cracks in cast billets and edge cracks in rolled products. Therefore, the sulfur content should be controlled to be ≤0.020%.
[0021] Alt (Al): It can fix free nitrogen in steel, improving the low-temperature toughness of the steel strip substrate and the weld heat-affected zone. Simultaneously, when the substrate is zinc / zinc-aluminum-magnesium coated, Al can increase the brightness of the coating and reduce oxidation and zinc ash formation on the zinc melt surface. However, excessive aluminum will affect the adhesion of the zinc / zinc-aluminum-magnesium coating and damage the coating quality. Therefore, the Alt content should be controlled between 0.015-0.045%.
[0022] Ti readily forms carbonitrides with C and N elements. Combined with controlled rolling and cooling processes, it can achieve the precipitation of nanoscale carbonitride particles, suppressing excessive austenite grain growth during slab heating and rolling, thus refining the grains and improving the low-temperature toughness of the matrix. Simultaneously, through proper matching with the subsequent cold rolling annealing process, it fully utilizes its pinning effect, leaving more room for exploring subsequent cold rolling annealing performance. Considering alloy cost, the Ti content is therefore controlled between 0.032% and 0.050%.
[0023] This invention provides a method for preparing low-cost, high-performance titanium-containing low-carbon Q235 hot-rolled steel strip for photovoltaic brackets, comprising the following steps: KR pre-desulfurization of molten iron, primary smelting in a converter or electric furnace, ladle refining, soft stirring, continuous casting of slabs, reheating of slabs, controlled rolling, controlled cooling, and coiling. The chemical composition and mass percentage of the steel billet obtained from the smelting and continuous casting processes are: C: 0.07-0.11%, Si: ≤0.10%, Mn: 0.35-0.50%, P: 0.08-0.1%, S: ≤0.020%, Alt: 0.015-0.045%, Ti: 0.032-0.050%; the balance being iron and unavoidable impurities.
[0024] The heating process is set with a billet exit temperature of 1060-1180℃ and a furnace time of ≥90min, with a further preferred furnace time of 90-120min.
[0025] The rolling process includes roughing and finishing. Roughing is performed in 3-7 passes. The exit temperature of the roughing stage is set at 1000-1050℃ to roll the billet into an intermediate billet with a thickness of 30-45mm. Then, it is continuously hot rolled in 5, 6 or 7 stands. The entry temperature of the finishing stage is set at 950-1040℃, and the final rolling temperature is 830-890℃.
[0026] The cooling and winding process adopts a full laminar flow cooling process, with a winding temperature of 580-650℃.
[0027] Furthermore, the continuous casting process employs full-process protective pouring, resulting in steel billet thicknesses of 150-200mm.
[0028] Furthermore, the intermediate billet thickness is 30-45mm. In order to ensure the performance of the steel strip and reduce the temperature difference between the head and tail of the intermediate billet, a hot rolling box is used to keep the intermediate billet warm and homogenize it.
[0029] Furthermore, the deformation amount in the first pass of rough rolling should not be less than 20%, and the cumulative deformation amount should be controlled at around 65-75%; the cumulative deformation amount in finish rolling should be controlled at around 55-65%, and the thickness of the intermediate billet can be appropriately increased to ensure the deformation amount.
[0030] The resulting steel strip product has a yield strength ≥390MPa, a tensile strength of 420-640MPa, an elongation after fracture ≥27%, and a microstructure of fine and uniform ferrite with a small amount of pearlite and a grain size of 10.5-11.5.
[0031] Compared with the prior art, the present invention has the following advantages:
[0032] 1. This invention provides a low-cost, easily implemented low-carbon, low-silicon, micro-manganese, and micro-titanium composition system. While ensuring the basic strength of the steel strip, it possesses high surface quality and relatively soft rollability, creating better control conditions for subsequent cold rolling and galvanized aluminum-magnesium / zinc-aluminum / zinc coating. This composition design avoids the potential hot cracking risks that may occur when the carbon content falls within the peritectic zone in medium- and high-carbon composition designs, ensuring good edge and corner quality of the cast billet. The cast billet does not require finishing on the ground and can be directly charged into the furnace online, reducing energy consumption and shortening the process flow. Simultaneously, it avoids the problems that may arise in the cold rolling process due to high carbon content, such as high cold rolling deformation resistance, inability of the mill to handle small loads, poor rolling rhythm stability, and low rolling efficiency. Furthermore, this composition design does not excessively pursue ultra-low carbon in order to achieve high cold rolling conditions. Currently, steel mills mostly require a deep decarburization process (RH) to achieve ultra-low carbon, resulting in a lengthy process and the need to add more manganese, titanium, and other alloys to compensate for strength loss, increasing process and alloy costs. This composition is designed with low cost and simple operation process, conforms to the actual steelmaking practices of most steel mills in China, and has strong scalability.
[0033] 2. The rolling process provided by this invention is simple and easy to implement. Because Ti is added to the composition design, the content of C, Si and Mn is reduced, which increases the solidification point of the continuous casting billet. The billet can be solidified without reducing the superheat temperature during continuous casting. Furthermore, hot charging and hot delivery can be adopted. After heating in the furnace on the line, the subsequent rolling process can be carried out directly, which reduces energy consumption, shortens the billet turnover cycle, and promotes fast-paced and high-efficiency production.
[0034] 3. This invention adds a small amount of titanium alloy during smelting. The effect of titanium on the mechanical properties of steel depends on its morphology. Titanium readily combines with nitrogen and carbon in steel to form Ti compounds. Because large-sized, four-sided TiN molecules are more likely to precipitate in molten steel at high temperatures, they can grow to the micrometer level under certain temperature conditions. This not only fails to provide precipitation strengthening but also transforms into inclusions, disrupting the continuity of the matrix, resulting in alloy waste and performance loss. Therefore, this invention employs argon gas stirring. Furthermore, since nitrogen has an atomic radius of 0.8 μm and dissolves in molten steel in atomic form, the higher the temperature of the molten steel, the lower the nitrogen solubility. Based on on-site investigations at the steelmaking site, it was found that when the final carbon extraction temperature was below 1620℃, the nitrogen content did not increase significantly with temperature, but when the final temperature was above 1620℃, the nitrogen content in the molten steel increased significantly. Therefore, this invention adopts low-temperature tapping, i.e., the billet tapping temperature is 1060-1180℃; during continuous casting, full-process protective casting is adopted to prevent the mixing of alloy materials, while scrap steel is cleaned and baked. Without adding other purification processes such as vacuum degassing (i.e., without increasing the cost of nitrogen control processes), through management methods, nitrogen-containing gases or materials are reasonably controlled to enter the molten steel, thereby improving the effective utilization of Ti and reducing smelting energy consumption.
[0035] 4. TiC microparticles can inhibit steel grain growth and have a significant impact on ferrite grain refinement. They only slowly dissolve into the iron solid solution when heated to above 1000℃. The morphology of titanium compounds depends on the carbon-to-titanium ratio and the heat treatment method. This invention aims to improve the utilization rate of effective Ti and promote its precipitation in the form of fine, dispersed TiC. By controlling the C to Ti content ratio to be stable at 1.5-3.0, combined with controlled rolling and cooling processes (low finishing rolling temperature and laminar flow cooling), the efficient precipitation of nano-sized TiC is promoted, effectively improving the utilization of effective Ti.
[0036] 5. This invention fully utilizes the corrosion resistance of phosphorus to improve the steel matrix. Without adding any production steps, it enhances the corrosion resistance of the steel strip matrix, resulting in a steel strip with more than twice the corrosion resistance of ordinary steel strips of the same strength level. This effectively reduces the amount of post-galvanizing, lowers galvanizing costs, improves economic efficiency, and is more environmentally friendly. Furthermore, by leveraging the low toughness and plasticity requirements of the extremely thin-gauge steel strip, it effectively balances the potential cold bending cracking failure of high-phosphorus steel. Simultaneously, it reduces the dephosphorization burden on the converter, decreasing the amount of dephosphorizing lime added by more than 15 kg / ton, thus lowering smelting costs.
[0037] 6. This invention adopts a low-carbon, low-silicon, micro-manganese, and micro-titanium composition system design, which significantly reduces the amount of C and Mn added. Through fine grain strengthening and precipitation strengthening, the welding performance of the steel strip is optimized while ensuring strength, laying a solid foundation for ensuring the welding quality of cold-bending forming after cold rolling and annealing of the steel strip.
[0038] The above-described technical solutions of the present invention can be combined with each other to achieve more preferred combinations; other innovations and advantages of the present invention can be obtained through the contents specifically pointed out in the embodiments and accompanying drawings. Attached Figure Description
[0039] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0040] Figure 1 This is a metallographic image of the steel strip prepared in Example 1 of the present invention with a scale of 100 μm.
[0041] Figure 2 This is a metallographic image of the steel strip prepared in Example 2 of the present invention with a scale of 100 μm.
[0042] Figure 3 This is a scanning electron microscope (SEM) image of the steel strip prepared in Example 1 of the present invention, with a scale of 25 μm.
[0043] Figure 4 This is a scanning electron microscope (SEM) image of the steel strip prepared in Example 2 of the present invention, with a scale of 10 μm.
[0044] Figure 5 This is a scanning electron microscope image of the steel strip prepared in Example 1 of the present invention with a scale of 1 μm, showing small-sized TiC precipitates.
[0045] Figure 6 The steel strip prepared in Example 1 of this invention Figure 5 The corresponding energy spectrum Figure 1 .
[0046] Figure 7 The steel strip prepared in Example 1 of this invention Figure 5 The corresponding energy spectrum Figure 2 . Detailed Implementation
[0047] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions of the embodiments of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this invention.
[0048] This invention provides a low-cost, high-performance photovoltaic support structure using titanium-containing low-carbon Q235 hot-rolled steel strip. The chemical composition and mass percentages are as follows: C: 0.07-0.11%, Si: ≤0.10%, Mn: 0.35-0.50%, P: 0.08-0.1%, S: ≤0.020%, Alt: 0.015-0.045%, Ti: 0.032-0.050%; the balance being iron and unavoidable impurities. Production follows the steps of KR pre-desulfurization of molten iron, primary smelting in a converter or electric furnace, ladle refining, soft stirring, continuous casting of slabs, reheating of slabs, controlled rolling, controlled cooling, and coiling. The specific steps are as follows:
[0049] (1) Hot metal KR pre-desulfurization: Hot metal desulfurization strictly follows the process specifications, and the sulfur content of hot metal is controlled below 0.020%. After desulfurization is completed, the slag on the surface of the hot metal is removed.
[0050] (2) Smelting process: Smelting is carried out according to the chemical composition of the product, and pure molten steel is obtained through clean steel smelting technology;
[0051] (3) Continuous casting process: molten steel is continuously cast to obtain a continuous casting billet. During the continuous casting process, constant casting speed control is adopted, and the entire process is protected during pouring to ensure good billet quality. The billet thickness is 175mm.
[0052] (4) Heating process: The billet is sent to the heating furnace for heating. In order to ensure that the alloying elements are fully dissolved and to avoid grain coarsening, the billet exit temperature is set to 1060-1180℃ and the furnace time is ≥90min.
[0053] (5) Rolling process: including roughing and finishing rolling. The roughing stage adopts 5 passes of rolling, with an exit temperature of 1010-1050℃ and an intermediate billet thickness of 30-45mm. The finishing stage achieves a certain degree of grain refinement through rolling temperature control. The finishing rolling entry temperature is 950-1040℃, the final rolling temperature is 830-890℃, and the thickness of the plate after rolling is 3.0-4.0mm.
[0054] (6) Cooling and winding process: The whole process is laminar flow cooling process, and the winding temperature is 580-650℃.
[0055] Examples 1-5 all use the above-described production method to prepare low-cost, high-performance photovoltaic bracket titanium-containing low-carbon Q235 hot-rolled steel strip. The chemical composition and process parameters of each example are shown in Table 1 and Table 2, respectively.
[0056] Table 1. Chemical composition (wt%) of titanium-containing low-carbon Q235 hot-rolled steel strip for low-cost, high-performance photovoltaic brackets in various embodiments.
[0057] 1 0.1 0.02 0.4 0.1 0.005 0.032 0.019 margin 2 0.08 0.05 0.38 0.09 0.005 0.041 0.029 margin 3 0.09 0.03 0.38 0.08 0.005 0.044 0.033 margin 4 0.08 0.03 0.38 0.08 0.007 0.041 0.038 margin 5 0.08 0.03 0.37 0.1 0.005 0.04 0.04 margin 6 0.08 0.03 0.37 0.1 0.005 0.04 0.04 margin 7 0.09 0.04 0.38 0.09 0.006 0.041 0.038 margin 8 0.09 0.04 0.38 0.1 0.006 0.041 0.038 margin 9 0.09 0.05 0.37 0.1 0.002 0.04 0.033 margin 10 0.09 0.05 0.38 0.09 0.004 0.039 0.034 margin
[0058] Table 2 Main process parameters of each embodiment
[0059]
[0060]
[0061] The titanium-containing low-carbon Q235 hot-rolled steel strips used for low-cost, high-performance photovoltaic brackets in Examples 1-10 were tested, and their key performance characteristics are shown in Table 3. Figure 1 , 3 As shown in Figures 5 and 6, the metallographic structure and scanning electron microscope (SEM) image of the steel strip prepared in Example 1 of this invention are shown. Figure 2 , 4 As shown, the metallographic structure and scanning electron microscope (SEM) image of the steel strip prepared in Example 2 of this invention are shown. Figure 6 , 7 The steel strip prepared in Example 1 of the present invention is shown. Figure 5 The corresponding energy spectrum.
[0062] Table 3 Key performance characteristics of titanium-containing low-carbon Q235 hot-rolled steel strip for high-cost, high-performance photovoltaic brackets in various embodiments.
[0063]
[0064]
[0065] All aspects not described in detail in this invention can be covered using conventional technical knowledge in the field.
[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to the embodiments, those skilled in the art should understand that modifications or equivalent substitutions to the technical solutions of the present invention do not depart from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A hot-rolled steel strip for photovoltaic brackets, characterized in that, The hot-rolled steel strip used for photovoltaic brackets comprises, by mass percentage: C: 0.07-0.11%, Si: ≤0.10%, Mn: 0.35-0.50%, P: 0.08-0.1%, S: ≤0.020%, Alt: 0.015-0.045%, Ti: 0.032-0.050%; the balance being iron and unavoidable impurities. The content ratio of C to Ti is controlled between 1.5 and 3.0; The method for preparing the hot-rolled steel strip for photovoltaic brackets includes the following steps: Hot metal pre-desulfurization, converter or electric furnace primary smelting, ladle refining, slab continuous casting, slab reheating, controlled rolling, controlled cooling, coiling; In the reheating of the slab, the heating process is set with a billet exit temperature of 1060-1180℃ and a furnace time of ≥90min. In the continuous casting of the slab, the continuous casting process adopts full-process protective pouring, and the thickness of the steel billet is 150-200mm. The controlled rolling process includes roughing and finishing. Roughing is performed in 3-7 passes, with the exit temperature set at 1000-1050℃. The billet is rolled into an intermediate billet with a thickness of 30-45mm. To ensure the performance of the steel strip and reduce the temperature difference between the head and tail of the intermediate billet, a hot rolling box is used to keep the intermediate billet warm and homogenize it. Then, it is continuously rolled in 5-7 stands. The entry temperature for the finishing stage is set at 950-1040℃, and the final rolling temperature is set at 830-890℃. In the controlled rolling process, the deformation amount in the first pass of roughing is not less than 20%, and the cumulative deformation amount is controlled between 65% and 75%; the cumulative deformation amount in finishing rolling is controlled between 55% and 65%. The cooling and winding process adopts a full laminar flow cooling process, with a winding temperature of 580-650℃. The photovoltaic bracket is manufactured using hot-rolled steel strip as raw material through cold rolling, annealing, hot-dip galvanizing / zinc-aluminum-magnesium, and cold bending. The hot-rolled steel strip used for the photovoltaic support has a yield strength ≥390MPa, a tensile strength of 420-640MPa, an elongation after fracture ≥27%, a microstructure of ferrite + pearlite, and a grain size of 10.5-11.5.
Citation Information
Patent Citations
Controlled rolling and controlled cooling technique for improving performance of Q235 steel plate
CN103343209A
Hot-dipped aluminum-zinc alloy steel plate and manufacturing method thereof
CN104060165A
Preparation method of high-strength photovoltaic steel
CN116657026A
